2019
DOI: 10.1038/s41467-019-09992-3
|View full text |Cite
|
Sign up to set email alerts
|

Lobular architecture of human adipose tissue defines the niche and fate of progenitor cells

Abstract: Human adipose tissue (hAT) is constituted of structural units termed lobules, the organization of which remains to be defined. Here we report that lobules are composed of two extracellular matrix compartments, i.e., septa and stroma, delineating niches of CD45−/CD34+/CD31− progenitor subsets characterized by MSCA1 (ALPL) and CD271 (NGFR) expression. MSCA1+ adipogenic subset is enriched in stroma while septa contains mainly MSCA1−/CD271− and MSCA1−/CD271 high progenitors. CD271 marks myof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…In adipose tissue, TCs/CD34+SCs are widely distributed in the septa and to a lesser extent in intralobular regions ( Figure 1 A). This distribution is important because different progenitor roles have been attributed to these cells, depending on their septal or intralobular location [ 18 ] (see below). In intralobular regions, TCs/CD34+SCs show a small somatic body and long, thin processes, which extend alongside adipocytes ( Figure 1 B–D) and the microvasculature ( Figure 1 E,F).…”
Section: Tcs/cd34+scs In Normal Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…In adipose tissue, TCs/CD34+SCs are widely distributed in the septa and to a lesser extent in intralobular regions ( Figure 1 A). This distribution is important because different progenitor roles have been attributed to these cells, depending on their septal or intralobular location [ 18 ] (see below). In intralobular regions, TCs/CD34+SCs show a small somatic body and long, thin processes, which extend alongside adipocytes ( Figure 1 B–D) and the microvasculature ( Figure 1 E,F).…”
Section: Tcs/cd34+scs In Normal Adipose Tissuementioning
confidence: 99%
“…Two progenitor subsets of CD34+ cells (TCs/CD34+SCs) in lobules of adipose tissue have recently been described depending on septal or intralobular location [ 18 ]. CD34+ cells in fibrous septa are predominant myofibroblast precursors, while intralobular CD34+ cells have adipogenic capacity [ 18 ]. Different TC/CD34+SC behaviour in repair has also been described depending on CD34 location [ 26 ], an issue that requires further study.…”
Section: General Considerations About the Behaviour Of Tcs/cd34+scmentioning
confidence: 99%
“…In addition, their characterization revealed that they were endowed with distinct adipose differentiation potentials, i.e., the highly adipogenic progenitors identified as CD36+/CD34+/MSCA1+ (i.e., PPBT+) were preferentially located in the stroma. In contrast, the MSCA1− progenitors displayed a fibrous phenotype with MSCA1−/CD271− cells in the septa and MSCA1−/CD271 high found in both compartments [56].…”
Section: Distinct Adipose Progenitors Raise Fat Pads With Different Fmentioning
confidence: 83%
“…The lobules as structural units within human AT depots are composed of two ECM compartments, stroma and septa. This was proposed to delineate the niches of progenitor subsets: the stromal vascular fraction (SVF) containing AT progenitors (APs) (CD45 − CD34 + CD31 − ALPL + ) and the fibrous septa mostly inhabited by myofibroblast progenitors (CD45 − CD34 + CD31 − CD271 high ), which are distributed differently in SAT and VAT (Estève et al, 2019). De novo adipogenesis takes place in proximity to the vasculature, particularly in the tunica media and tunica adventitia, where pericytes and fibroblasts share a similar mesenchymal phenotype with overlapping expressions of PDGFRα (fibroblasts) and PDGFRβ (pericytes) (Jiang et al, 2014;Guimarães-Camboa and Evans, 2017;Sun et al, 2019).…”
Section: Adipose Tissue Niche Constituentsmentioning
confidence: 99%